THE RELATIONSHIP OF INTERTEXTUAL EMANCIPATION OF WOMEN IN THE “DYAH PITALOKA” NOVEL AND BOOK OF “HABIS GELAP TERBITLAH TERANG” - Ema Damayanti (IKIP Siliwangi, 2020)
The purpose of this study is to compare and obtain the meaning of the relationship between the two texts about the value of emancipation so that conclusions can be obtained about the values of emancipation that can be used as an example for women to be used to get more for the state and state. The Emancipation Values examined in this study are: 1) Critical to the socio-cultural environment in society, 2) Women must have Attitudes and Wills 3) Refuse Treatment of Women 4) Love to learn and be educated, 5) Concern for community and nation research. The research method used is a descriptive qualitative method by examining the values of emancipation from the two texts, looking for similarities and differences then analyzed intertextually by the authors' meanings as instruments and literary publishers. The results of the study showed that the value of emancipation owned by Dyah Pitaloka in the DP and Kartini in HGTT had many similarities and found no differences. Dyah Pitaloka and Kartini both wanted women to be empowered, willing, and chosen in many ways. Women also need to be invited to the same gender, given the opportunity in education and public roles. Women also need to be educated so that they can benefit the children and the nation. Kartini and Dyah Pitaloka both want to work together with men and also with the community. From the point of feminism, they embrace moderate feminism. This research is useful as educational material for women.Keywords: Intertextual Studies, Women's Emancipation, Novel “Dyah Pitaloka”, Texts “Habis Gelap Terbitlah Terang”